ANALYSIS OF VARIABILITY AND GENETIC PARAMETERS FOR YIELD ATTRIBUTES IN SABITA/SAMBAMAHSURI DERIVATIVES OF RICE ( OF RICE (Orysa sativa Orysa sativa L.) GENOTYPES L.) GENOTYPES - ANSHUMAN TIWAR; B. K. SENAPATI, SANJUKTA MUNDA (The Bioscan, 2018)
Study on variability analysis and genetic parameters for yield attributing characters was carried out using twentythree recombinant inbred lines of Sabita/Sambamahsuri derivatives with four check varieties viz. Swarna sub-1, Dhanarasi, Sambamahsuri and Sabita in RBD with two replications. Statistical analysis carried out for the estimation of GCV, PCV, heritability (BS) and genetic advance for all characters. The genotypes S11(32.52), S23(31.63), S16(31.25), S12(30.74), S15(30.68) and S2(30.06) were superior in grain yield per plant (g) with the margin of 11.36%, 8.32%, 7.02%, 5.27%, 5.06% and 2.95% respectively as compared to best check varieties. S1 , S2 , S3 , S11, S19 and S23 were superior for most of the yield determining traits viz., grain yield per plant, panicle weight, panicle length, number of secondary branches per panicle, number of florets per panicle, number of grains per panicle, harvest index as compared to check varieties. High estimates of GCV and PCV were obtained for panicle weight (15.019 and 17.632) followed by number of floret per panicle (10.285 and 11.122). High heritability was observed for most of the characters under study. High heritability coupled with high GA% was observed for panicle weight and number of floret per panicle. These characters are governed by additive gene action and one should go for direct selection for these traits.